Development of anodised aluminium oxide nanostructure from Al-Mn alloy - Voon Chun Hong (School of Materials Engineering, University Malaysia Perlis, 2013)
This study was divided into two parts. The first part of the study was focuses on the synthesis of well ordered porous AAO by using oxide dissolution treatment. The porous AAO was formed by anodising of 99.99% aluminium in 0.3 M oxalic acid at 15 c for 15 minutes. Anodised substrates were subjected t oxide dissolution treatment by immersing in stirred mixture of chromic acid and phosphoric acid. The efffect of oxide dissolutuion treatment on the morphology and regulrity of porous AAO was studied by using scanning electron microscope.